Genome-Wide Identification and Characterization of Four Gene Families Putatively Involved in Cadmium Uptake, Translocation and Sequestration in Mulberry - Fan, Wei; Liu, Changying; Cao, Boning; Qin, Meiling; Long, Dingpei; Xiang, Zhonghuai; Zhao, Aichun (Frontiers in Plant Science, 2018)
The zinc-regulated transporters, iron-regulated transporter-like proteins (ZIPs), the natural resistance and macrophage proteins (NRAMP), the heavy metal ATPases (HMAs) and the metal tolerance or transporter proteins (MTPs) families are involved in cadmium (Cd) uptake, translocation and sequestration in plants. Mulberry (Morus L.), one of the most ecologically and economically important (as a food plant for silkworm production) genera of perennial trees, exhibits excellent potential for remediating Cd-contaminated soils. However, there is no detailed information about the genes involved in Cd2+ transport in mulberry. In this study, we identified 31 genes based on a genome-wide analysis of the Morus notabilis genome database. According to bioinformatics analysis, the four transporter gene families in Morus were distributed in each group of the phylogenetic tree, and the gene exon/intron structure and protein motif structure were similar among members of the same group. Subcellular localization software predicted that these transporters were mainly distributed in the plasma membrane and the vacuolar membrane, with members of the same group exhibiting similar subcellular locations. Most of the gene promoters contained abiotic stress-related cis-elements. The expression patterns of these genes in different organs were determined, and the patterns identified, allowing the categorization of these genes into four groups. Under low or high-Cd2+ concentrations (30 μM or 100 μM, respectively), the transcriptional regulation of the 31 genes in root, stem and leaf tissues of Morus alba seedlings differed with regard to tissue and time of peak expression. Heterologous expression of MaNRAMP1, MaHMA3, MaZIP4 and MaIRT1 in Saccharomyces cerevisiae increased the sensitivity of yeast to Cd, suggested that these transporters had Cd transport activity. Subcellular localization experiment showed that the four transporters were localized to the plasma membrane of yeast and tobacco. These results provide the basis for further understanding of the Cd tolerance mechanism in Morus, which can be exploited in Cd phytoremediation.